(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper presents the development of a 3D laser scanning system that can produce an indoor navigation map for an automated guided vehicle. The system uses only a 1D Light Detection and Ranging (LiDAR) as a measuring device and two stepper motors for positioning. Several tests are performed to determine the best trade-off between the time needed for the scan and the required resolution to produce an indoor navigation map, and the relationship between these variables is presented.